Cellulose-based magnetoelectric composites - Zong, Yan (2017)
Since the first magnetoelectric polymer composites were fabricated more than a decade ago, there has been a reluctance to use piezoelectric polymers other than poly(vinylidene fluoride) and its copolymers due to their well-defined piezoelectric mechanism and high piezoelectric coefficients that lead to superior magnetoelectric coefficients of > 1 V.cm−1 Oe−1. This is the current situation despite the potential for other piezoelectric polymers, such as natural biopolymers, to bring unique, added-value properties and functions to magnetoelectric composite devices. Therefore, we demonstrate a cellulose-based magnetoelectric laminate composite that produces considerable magnetoelectric coefficients of  1.5 V.cm−1 Oe−1 at low magnetic fields. Simple solution processing induces alignment of cellulose fibrils, leading to amplification of nanoscale piezoelectric domains and the magnetoelectric coefficient. The magnetoelectric frequency line shape shows a Fano-resonance that is ubiquitous in the field of physics, such as photonics, though never experimentally observed in magnetoelectric composites. This fundamental phenomenon is due to the inherent chemical structure of cellulose and important for understanding the magnetoelectric mechanisms. The work successfully demonstrates the concept of exploring new advances in using biopolymers in magnetoelectric composites, particularly cellulose, which is increasingly employed as a renewable, low-cost, easily processable and degradable material.